Retracted: Baicalin prevents tumor necrosis factor‐α−induced apoptosis and dysfunction of pancreatic β‐cell line Min6 via upregulation of miR‐205. Issue 10 (30th July 2018) - You, Wenjun; Wang, Kun; Yu, Changhong; Song, Lijuan
Abstract: Baicalin (BAI), one major flavonoid from Scutellaria baicalensis, possesses anticancer and anti‐inflammatory properties. However, the effect of BAI on diabetes mellitus has not been investigated. This study explored the antidiabetic effect of BAI on pancreatic β‐cell line Min6. Min6 cells were treated with tumor necrosis factor‐α (TNF‐α) to mimic β‐cell destruction in type 1 diabetes mellitus. The effects of BAI on viability and apoptosis of Min6 cells were analyzed by the cell counting kit‐8 assay and Annexin V‐fluoresceine isothiocyanate/propidium iodide staining method. The insulin secretion of Min6 cells was determined using radioimmunoassay. Expression of apoptosis‐associated proteins and inducible nitric oxide synthase (iNOS), and activation of phosphatidylinositol 3ʹ‐kinase/protein kinase B (PI3K/AKT) and nuclear factor ΚB (NF‐κB) pathways were analyzed by Western blot analysis. Relative microRNA‐205 (miR‐205) expression was determined by quantitative real time polymerase chain reaction. TNF‐α treatment inhibited cell growth and insulin secretion, but promoted iNOS expression. All of these effects were reversed by BAI treatment. BAI promoted viability; suppressed apoptosis; regulated caspase‐3, B‐cell lymphoma 2 and Bcl‐2‐associated X protein; decreased iNOS level; and increased insulin production. BAI protected Min6 cells by upregulating miR‐205. Besides, the Min6 cell‐protective effect of BAI was PI3K/AKT pathway and NF‐κB pathway dependent. BAI activated the PI3K/AKT pathway and inhibited the NF‐κB pathway by regulating miR‐205. In conclusion, BAI protected Min6 cells from TNF‐α‐induced injury by upregulating miR‐205, which acts, at least in part, via activation of the PI3K/AKT pathway and inactivation of the NF‐κB pathway. Abstract : Baicalin (BAI) activated the PI3K/AKT pathway and inhibited the NF‐κB pathway by regulating miR‐205. BAI protected Min6 cells from tumor necrosis factor‐α−induced injury by upregulating miR‐205, which might be due to the activation of the PI3K/AKT pathway and inactivation of the NF‐κB pathway.